Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1037/men0000111
|View full text |Cite
|
Sign up to set email alerts
|

Help-seeking stigma among men in the military: The interaction of restrictive emotionality and distress.

Abstract: Stigma is one of the most commonly cited barriers toward seeking mental health services for men in the military. Although factors like socialized masculine norms (i.e., restrictive emotionality) and levels of distress are associated with stigma in civilian samples, less is known about these factors for men in the military. This study examines how distress and restrictive emotionality relate to help-seeking stigma in a sample of 271 men in the military. Results indicate that distress, restrictive emotionality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…Men who irrevocably adhere to strong masculine beliefs have an even higher likelihood of not participating in primary preventive care regardless of increased wealth, income, or occupational status; therefore, targeted messaging early on in a young man's life is paramount. 42 For example, reframing stigmatizing messages like "boys shouldn't cry" to something more along the lines of "Strong men take time to take care of their health so they can take care of their family" or "It's ok to show emotion," can help combat the hegemonic masculinity that often precludes men from proactively participating in healthcare. Ideally, these messages would be delivered from a foundational perspective from a boy's earliest interactions with the healthcare system.…”
Section: Targeted Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Men who irrevocably adhere to strong masculine beliefs have an even higher likelihood of not participating in primary preventive care regardless of increased wealth, income, or occupational status; therefore, targeted messaging early on in a young man's life is paramount. 42 For example, reframing stigmatizing messages like "boys shouldn't cry" to something more along the lines of "Strong men take time to take care of their health so they can take care of their family" or "It's ok to show emotion," can help combat the hegemonic masculinity that often precludes men from proactively participating in healthcare. Ideally, these messages would be delivered from a foundational perspective from a boy's earliest interactions with the healthcare system.…”
Section: Targeted Interventionsmentioning
confidence: 99%
“…One example of a successful, targeted message is that of cell-phone applications that will send weekly tips and education on preventive practices and sexual health, in addition to notifications regarding healthcare directly to the patient via their mobile device. 32,42,44 Additionally, for men who are less technologically inclined, tailoring healthcare messages to patient populations in formats they interface with regularly, such as sporting events, barbershops or other social venues, these platforms can be successful in engaging patients in health-promoting behaviors. 31,45 Finally, tailoring healthcare messages to men's spouses/partners may prove beneficial as data from national health surveys have found that partnered men were more likely than unpartnered men to undergo a primary health care visit and screenings the last twelve months.…”
Section: Targeted Interventionsmentioning
confidence: 99%
“…Fears about being seen as weak (62%) and being judged (48%) are commonly cited reasons for concealing suicidal ideations (Hom et al, 2017a). Stigmatization fears brought on by gender role conflict may disproportionally affect men employed in professions noted for adhering to traditional male gender norms, such as military service members and law enforcement officers (Heath et al, 2017;Hom et al, 2017b). In a study examining perceptions of mental illness stigma in police departments, 62% of officers believed that most of their peers would expect to experience discrimination if they disclosed a history of mental illness (Stuart, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There have also been initiatives to reduce the stigma associated with mental health conditions to encourage service members to seek assistance independently (Morin 2017; Quartana 2014). Despite these efforts, service members continue to report avoidance of health care (Heath et al 2017; Sharp et al 2015). In fact, stigma has been shown to be a barrier to completing a course of mental health treatment among military service members (Britt et al 2015).…”
Section: Introductionmentioning
confidence: 99%